Global Analysis and Comparison of the Transcriptomes and Proteomes of Group A Streptococcus Biofilms - Freiberg, Jeffrey A. (mSystems, 2016)
To gain a better understanding of the genes and proteins involved in group A Streptococcus (GAS; Streptococcus pyogenes) biofilm growth, we analyzed the transcriptome, cellular proteome, and cell wall proteome from biofilms at different stages and compared them to those of plankton-stage GAS. Using high-throughput RNA sequencing (RNA-seq) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) shotgun proteomics, we found distinct expression profiles in the transcriptome and proteome. A total of 46 genes and 41 proteins showed expression across the majority of biofilm time points that was consistently higher or consistently lower than that seen across the majority of planktonic time points. However, there was little overlap between the genes and proteins on these two lists. In line with other studies comparing transcriptomic and proteomic data, the overall correlation between the two data sets was modest. Furthermore, correlation was poorest for biofilm samples. This suggests a high degree of regulation of protein expression by nontranscriptional mechanisms. This report illustrates the benefits and weaknesses of two different approaches to global expression profiling, and it also demonstrates the advantage of using proteomics in conjunction with transcriptomics to gain a more complete picture of global expression within biofilms. In addition, this report provides the fullest characterization of expression patterns in GAS biofilms currently available. IMPORTANCE Prokaryotes are thought to regulate their proteomes largely at the level of transcription. However, the results from this first set of global transcriptomic and proteomic analyses of paired microbial samples presented here show that this assumption is false for the majority of genes and their products in S. pyogenes. In addition, the tenuousness of the link between transcription and translation becomes even more pronounced when microbes exist in a biofilm or a stationary planktonic state. Since the transcriptome level does not usually equal the proteome level, the validity attributed to gene expression studies as well as proteomic studies in microbial analyses must be brought into question. Therefore, the results attained by either approach, whether RNA-seq or shotgun proteomics, must be taken in context and evaluated with particular care since they are by no means interchangeable.